Financial Literacy, Performance, And Welfare Of Msmes In Gianyar Regency - Putra, Gde Bagus Brahma; Ernawatiningsih, Ni Putu Lisa; Prastyadewi, Made Ika; Astiti, Ni Putu Yeni (Jurnal Ekonomi Kuantitatif Terapan; Vol 18 No 1 (2025): Vol. 18, No. 1, FEBRUARI 2025 (pp.1-149)DO - 10.24843/JEKT.2025.v18.i01.P04, 2025)
This study aims to 1). Analyzing the effect of financial literacy on the performance of MSMEs, 2). Analyzing the effect of financial literacy on the welfare of MSME actors, and 3). Analyzing the effect of MSME performance on the welfare of MSME actors. The research was conducted in Gianyar Regency and focused on 110 MSME actors. The data sources used are primary data from bamboo weaving crafters and secondary data from various relevant agencies. The analysis results show that financial literacy affects the performance and welfare of MSME actors, and performance also affects their welfare. The results of this analysis also show that good financial literacy will be able to improve the performance of MSMEs, especially in facing digital developments and various global challenges.